High-resolution infrared polarization spectroscopy and degenerate four wave mixing spectroscopy of methane - Richard, K; Ewart, P (2009)
High-resolution infrared polarization spectroscopy (IR-PS) and degenerate four wave mixing (IR-DFWM) spectroscopy of methane using a diode-seeded modeless laser (DSML) system are reported. Mid-infrared radiation around 3.3 μm is generated by difference frequency mixing of the single-mode output of the DSML around 0.634 μm with the frequency-doubled output of a single-mode Nd:YAG pump laser at 0.532 μm. Polarization spectroscopy signals in the forward geometry were generated in methane at around 5 Torr pressure. IR-PS spectra were recorded with a typical signal-to-noise ratio of 150:1 with methane pressures of at least 1 Torr. The line shape of the IR-PS signals was analysed to measure pressure broadening induced by nitrogen buffer gas yielding a value of 6.3±1.5 MHz∈Torr-1. IR-DFWM spectra of methane were generated in the counter-propagating pump geometry yielding Doppler-free signals with signal-to-noise ratios of typically 650:1. Signals were obtained at methane pressures down to less than 10 mTorr. A comparison of IR-PS and IR-DFWM is made indicating that IR-DFWM has some advantages over IR-PS in this spectral region in terms of sensitivity, signal-to-noise ratio and ease of use. The results illustrate the utility of the DSML for high-resolution nonlinear spectroscopy in the mid infrared. © 2009 Springer-Verlag.